The limits of party Congress and lawmaking in a polarized era - Curry, James M.; Lee, Frances E. (The University of Chicago Press, 2020)
"When a party achieves control of Congress, as the Republicans did from 2014 to 2018, to what extent is it able to bend legislative outcomes toward its policy preferences? Are parties in Congress capable of following through on their vision for public policy? Can they leverage their enhanced cohesion, as we have seen in the last decade or so and procedural power as the majority party in the House and the Senate, to enact their partisan programs? The authors argue that bipartisanship remains the key to legislative success, even in a time of partisan polarization. Even in the contemporary, partisan Congress, most laws-including landmark laws such as the recent criminal justice reform legislation-still pass with broad bipartisan support"--
Keywords: USA -- Congress; Parteiensystem; Gesetzgebung; United States / Congress; Legislative power / United States; Political parties / United States; POLITICAL SCIENCE / Government / General; Legislative power; Political parties; United States